Public spaces in the contemporary city: a (re)view - Souza, Andre Felix de (Geografares, 2018)
In the last decades, and especially since 1990, the theme of public spaces has definitely entered the agenda of the social sciences and of geography. With the present article, we seek to review some of this bibliography and, in particular, critically interrogate the socalled the end of public spaces thesis, that is, the argument that the public spaces of contemporary or postmodern cities would be going through a global process of “decay”, “regression” and “crisis”. Keywords: Public Spaces; Postmodern Cities.